Accessibility Of Tourist Objects In Vietnam Village In Sumber Agung Village, Kemiling District, Bandar Lampung City - Dayanti, Rizka Dwi; Utami, Rahma Kurnia Sri; Nugraheni, Irma Lusi; Miswar, Dedy (Universitas Lampung, 2025)
Kampoeng Vietnam, located in Sumber Agung, Kemiling District, Bandar Lampung City, is a natural tourist destination offering scenic landscapes but constrained by limited accessibility. This study aims to assess accessibility using six variables: alternative routes, travel distance, travel time, road conditions, transportation modes, and travel costs. A quantitative descriptive method was employed, with data collected through observation, documentation, and structured interviews. Spatial scoring analysis was applied to classify accessibility into three levels: high (>19), moderate (14–19), and low (8–13). The findings reveal that the site has three primary access routes, with 75% of respondents rating them positively. Travel distances were generally under 35 km (93%), and 75% of visitors reported travel times of less than one hour. Road surfaces were predominantly asphalt or damaged concrete (72%), and uneven terrain was noted by all respondents. All visitors relied on private land transportation, and 59% reported spending less than IDR 25,000 per visit. The overall accessibility score was 18, indicating a moderate level. The study concludes that improving road quality, providing public transportation options, and enhancing cost-efficiency are necessary to increase accessibility and visitor comfort.